Pt and Pt‐group transition metal 0D vacancy ordered halide perovskites: A review - Huilong Liu; Shubhra Bansal (EcoMat)
Abstract Lead halide perovskites (LHPs), have attracted considerable attention across various applications owing to their exceptional optoelectronic properties. However, the main challenge hindering the broad adoption of lead halide perovskites lies in their stability and toxicity. In this review, we summarize the outstanding properties of platinum (Pt) halide perovskites, with a particular focus on the stability and applications of Cs2PtI6 and its derivatives. Cs2PtI6 has shown promising efficiency for photovoltaic devices, as well as photoelectrochemical water splitting with stable behavior in acid or basic conditions. Cs2PtI6 also shows promise in gas sensing and thermoelectric devices. The emergence of 2D Pt (II) halide perovskites opens up new avenues for environmentally friendly materials for photonic and optoelectronic devices like room temperature phosphoresce and triplet‐triplet annihilation (TTA) based up‐conversion.